Cyprus : 2019 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Cyprus. (IMF Staff Country Reports; Country Report, 2019)
This 2019 Article IV Consultation with Cyprus discusses that following a period of very rapid growth in the aftermath of the economic crisis, growth is gradually settling in at a more sustainable but still relatively robust pace despite the external slowdown. Output is projected to rise by around 3 percent in 2019-20, supported by construction and services sectors. Good progress has been made in addressing domestic and external stability risks arising from legacies of the financial crisis. Sales of nonperforming loans (NPLs), amendments to the foreclosure and insolvency framework and resolution of a large systemic bank have helped strengthen bank balance sheets. Reversal of reforms to the foreclosure framework would hinder ongoing NPL resolution efforts and create risks for financial stability. Realization of contingent liabilities from the still weak banking sector or increased fiscal spending pressures could undermine investor confidence, raising interest costs and depressing growth. Cyprus needs to build on recent gains by advancing reforms to secure macroeconomic stability, enhance efficiency and strengthen productivity and growth potential.